A novel H2S releasing-monastrol hybrid (MADTOH) inhibits L-type calcium channels. (21st December 2020) - Braga, Taniris Cafiero; de Jesus, Itamar Couto Guedes; Soares, Kathleen Viveiros; Guatimosim, Silvia; da Silva Neto, Leonardo; da-Silva, Cristiane Jovelina; Modolo, Luzia Valentina; Menezes Filho, José Evaldo Rodrigues; Rhana, Paula; Cruz, Jader Santos; de Fátima, Ângelo
Abstract : A new alleged monastrol-H2 S releasing hybrid, named MADTOH, was designed based on the structure of monastrol (M ) and 5-(4-hydroxyphenyl)-3 H -1, 2-dithiole-3-thione (ADTOH ) and synthesized in 7.8% overall yield. Abstract : A new alleged monastrol-H2 S releasing hybrid, named MADTOH, was designed based on the structure of monastrol (M ) and 5-(4-hydroxyphenyl)-3 H -1, 2-dithiole-3-thione (ADTOH ) and synthesized in 7.8% overall yield. MADTOH was shown to be an H2 S donor under physiological conditions. In addition, the hybrid causes a decrease in global calcium transient in cardiomyocytes similar to nifedipine (NIFE ), taken as a positive control. Whole-cell voltage-clamp showed that MADTOH decreases L-type Ca 2+ current in isolated ventricular cardiomyocytes.